Inclusion, Equity and Access for Individuals with Disabilities Insights from Educators across World - Halder, Santoshi; Argyropoulos, Vassilios (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book offers a global and social examination of how disabilities are played out and experienced around the world. It provides multiple perspectives and insights on the area of inclusion and brings together various inclusive practices in action. The book documents perspectives from educational researchers and teacher educators through first-hand experience using cutting-edge research and conceptual understandings, thought processes, and reflections. The book brings together various methodologies to expose scientific truths in the area of disability and inclusion. Chapter authors utilize a self-reflective stance, representing state of the art theory and practice for exploring notions of disability. Authors examine cultural relational practices, common values and beliefs, and shared experiences for the purpose of helping cultural members and cultural strangers better understand interdependent factors. Each chapter is an attempt to unravel a thought provoking, comprehensive, and thorough understanding of the challenges and abilities of individuals with disabilities shaped by their own culture, society and country, re-engaging the promise of scientific research as a generative form of inquiry. The book is designed to be of use to a wide range of professionals; researchers, practitioners, advocates, special educators and parents providing information and or discussions on educational needs, health care provisions, and social services irrespective of country and culture.